1999
DOI: 10.1152/jappl.1999.87.1.183
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone in resting and exercising men. II. Effects on adrenocortical hormones

Abstract: Dexamethasone in resting and exercising men. II. Effects on adrenocortical hormones. J. Appl. Physiol. 87(1): 183-188, 1999.-This study presents the reactions of adrenocorticosteroids (cortisol and aldosterone) and sex steroids [testosterone, androstenedione, and dehydroepiandrosterone and its sulfate (DHAS)] 1) to a dexamethasone (Dex) treatment, which is expected to lower steroid levels via the ACTH blockade, and 2) to an exercise bout at maximal O 2 consumption, which is expected to increase steroid produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 31 publications
1
10
0
4
Order By: Relevance
“…In agreement with most of the studies conducted after either acute or short-term GC administration (Arlettaz et al 2006(Arlettaz et al , 2007(Arlettaz et al , 2008aLac et al 1999;Marquet et al 1999), we found a signiWcant decrease in both ACTH and DHEA basal values in our healthy women after 1 week of prednisone treatment, with no signiWcant increase from these basal concentrations during exercise. This demonstrates that short-term treatment with GC even at the therapeutic level induces a complete inactivation of the hypothalamic-pituitary-adrenal axis during submaximal exercise, irrespective of gender.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with most of the studies conducted after either acute or short-term GC administration (Arlettaz et al 2006(Arlettaz et al , 2007(Arlettaz et al , 2008aLac et al 1999;Marquet et al 1999), we found a signiWcant decrease in both ACTH and DHEA basal values in our healthy women after 1 week of prednisone treatment, with no signiWcant increase from these basal concentrations during exercise. This demonstrates that short-term treatment with GC even at the therapeutic level induces a complete inactivation of the hypothalamic-pituitary-adrenal axis during submaximal exercise, irrespective of gender.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the participants provided unstimulated saliva samples at rest, and, as reported previously in the literature, at 5 min post exercise (Engels et al 2003;Kraemer et al 1996;Volek et al 1997;Viru et al 1998). Nonetheless, according to Lac et al (1999), the rise in cortisol level will appear only after a minimal delay of 20 min. In line with this, Kirschbaum and Hellhammer Table 2 Power indices and heart rates PPO peak power output (using participants' best PPO from 6 sprints); Max FI% Greatest fatigue index value; APPO average peak power output (across sprints 1-6); AMPO average mean power output (across sprints 1-6); HR heart rate (1989) recommend that investigators should report more than one post exercise sample, and that, where possible, one sample should be obtained approximately 30 min after exercise.…”
Section: Discussionmentioning
confidence: 60%
“…Application of 10 -9 mol/l aldosterone also stimulated NHE (126±10% of control, n=45, P<0.05). This concentration of aldosterone is only slightly above the physiological one and can be easily observed under pathophysiological conditions with elevated aldosterone concentrations [5,8,14,27,29,33].…”
Section: Resultsmentioning
confidence: 88%